Consecutive Single‐Crystal‐to‐Single‐Crystal Isomerization of Novel Octamolybdate Anions within a Microporous Hybrid Framework with Robust Water Sorption Properties - Ruiz‐Bilbao, Estibaliz; Iturrospe, Amaia; Reinoso, Santiago; Artetxe, Beñat; Beobide, Garikoitz; San Felices, Leire; Lezama, Luis; Gutiérrez‐Zorrilla, Juan M.; Darwish, Shaza; Sensharma, Debobroto; Zaworotko, Michael J. (Angewandte Chemie, 2023)
The 3D hybrid framework [{Cu(cyclam)} 3 (κ‐Mo 8 O 27 )] ⋅ 14H 2 O ( 1 ) (cyclam=1,4,8,11‐tetraazacyclotetradecane) undergoes sequential single‐crystal‐to‐single‐crystal transformations upon heating to afford two different anhydrous phases ( 2 a and 3 a ). These transitions modify the framework dimensionality and enable the isomerization of κ‐octamolybdate (κ‐Mo 8 ) anions into λ ( 2 a ) and μ ( 3 a ) forms through metal migration. Hydration of 3 a involves condensation of one water molecule to the cluster to afford the γ‐Mo 8 isomer in 4 , which dehydrates back into 3 a through the 6 a intermediate. In contrast, 2 a reversibly hydrates to form 5 , exhibiting the same Mo 8 cluster as that of 1 . It is remarkable that three of the Mo 8 clusters (κ, λ and μ) are new and that up to three different microporous phases can be isolated from 1 ( 2 a , 3 a , and 6 a ). Water vapor sorption analyses show high recyclability and the highest uptake values for POM‐based systems. The isotherms display an abrupt step at low humidity level desirable for humidity control devices or water harvesting in drylands.